Tax Avoidance, Hidden Behind Corporate Social Responsibility: Moderating Role of Economic Freedom - Retnaningtyas Widuri; Vanness Hansen Tjoadinata; Marchello Koesoema; Dean Charlos Padji Dogi (International Journal of Organizational Behavior and Policy, 2026)
The purpose of this study is to examine whether Economic Freedom (EF) moderates the effect of Corporate Social Responsibility (CSR) on Tax Avoidance (TA). Using a panel of 285 listed firms from Indonesia, Australia, Singapore, the United States, and China over the period 2019–2023, we estimate multivariate regression models in which TA is proxied by the Effective Tax Rate (ETR) and the Cash Effective Tax Rate (CETR), CSR is proxied by the ESG Score, and EF is measured by the Heritage Economic Freedom Index. The empirical results show that higher CSR is associated with lower TA when TA is measured by ETR, while the interaction between CSR and EF is statistically insignificant across both TA measures. These findings suggest that CSR is generally consistent with lower tax avoidance, but that the moderating role of EF is weaker than expected in the post‑COVID‑19 period. The study contributes to the CSR–tax literature by incorporating a multi‑country post‑pandemic setting and by clarifying that EF does not systematically strengthen the CSR–TA relationship, thereby nuancing prior evidence on institutional moderators. Our results also offer policy and managerial implications for aligning CSR practices with transparent and responsible tax behaviour in different institutional environments.